46. CanCore: in Canada and Around the World - Friesen, Norm (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The current report provides an update on Report #11 and Report #40 in this series, describing the increasing range of international uses of the CanCore metadata for the indexing of learning objects.